(untitled) (Islas, 2021)
Spanish is a language with great possibilities of expressiveness, so the speaker of the Cuban variant of Spanish has various resources to articulate the weighting. In this way, the study of the superlative is current in linguistic research, where it includes all those phenomena that increase, expand and / or exaggerate, traits, qualities or communicative situations. This paper analyzes the expression of the superlative in the novel Tumbaga by Samuel Feijóo and, specifically, focuses on the textual level. The analysis of this novel means the search for popular and Cuban essences, as is the case of the expression of the superlative. In this sense, the objective is to describe the linguistic procedures that express the superlative at the textual level of the novel Tumbaga by Samuel Feijóo. The methodological foundation is based on authors such as Albelda Marco (2005 [2004] and 2014), Arboleda Granda (2012) and González Calvo (1984-1988) who precisely studies the superlative at the textual level. In the novel, different textual procedures that enhance the expressive content and take full significance in the communicative context are recognized.The following linguistic procedures stand out: superlative content by accumulation and superlative valuation; the profusion of linguistic procedures, such as the amplifying metaphor. The profusion of expressions and resources to superlativize at the textual level is evidenced, which also have a marked stylistic character.